Refugee Housing Accessibility with a Strategic Digital City Project (Global Journal of Human-Social Science, 2024)
Adequate housing is pivotal for the refugee s wellbeing demanding strategic urban management to facilitate their integration The research objective is to analyze housing access for adult refugees within the context of a strategic digital city focusing on adult refugees and city strategies as a subproject of the strategic digital city project The research methodology adopted is a case study in Curitiba the research employs both qualitative and quantitative techniques guided by a research protocol Results suggest that addressing housing access challenges entails more than mere provision it involves safeguarding rights stability integration and participation in public policies and municipal strategies within the strategic digital city framework and the right to the city These findings underscore the necessity for support services and robust collaboration among diverse stakeholders and public policies to tackle the multifaceted refugee issue thereby fostering their integration and well-being in the host society The conclusion emphasizes prioritizing concepts such as privacy and dignity in housing highlighting the urgent need for effective policies catering to refugees diverse needs Beyond economic and housing hurdles refugees encounter prejudice xenophobia and inequalities requiring not only governmental and NGO interventions but also active societal engagement To promote integration it is imperative to reevaluate housing costs ensure service accessibility and involve refugees in decision-making processes to formulate tailored policies acknowledging their experiences as valuable contributions to society
Keywords: refugees housing; city right; political science; social science; international immigration; human integration